Does psychological contract on work-family benefits improve employee commitment? - Mohamed Azim, Abdul Mutalib; Ahmad, Aminah; Omar, Zoharah; Silong, Abu Daud (Canadian Center of Science and Education, 2015)
The purpose of this study is to examine the role of work-family psychological contract fulfillment as a mechanism through which work-family factors affect employees’ organizational commitment. The data for this study were collected from media organization employees in Malaysia using self-administered questionnaires. The results indicate that work-family psychological contract fulfillment correlates significantly with work-family conflict, work-family facilitation and organizational commitment. Work-family psychological contract fulfillment has a mediating effect on the relationships between the work-family factors (work-family facilitation and work-family conflict) and organizational commitment. The results underscore the important role of work-family psychological contract fulfillment in improving organizational commitment. The findings point to the importance of organizations investing in work-family benefits since this investment has the potential of improving organizational commitment of employees. Organizations should plan for interventions that could reduce work-family conflict and enhance work-family facilitation. In future, there is a need for researchers to give more attention to work-family benefits in psychological contract research.